Decreased Case Fatality Rate of COVID‐19 in the Second Wave: A study in 53 countries or regions. Issue 2 (17th September 2020) - Fan, Guihong; Yang, Zhichun; Lin, Qianying; Zhao, Shi; Yang, Lin; He, Daihai
Abstract: The raw case fatality rate (CFR, the reported number of COVID‐19 deaths divided by the total number of cases) is an important indicator to quantify the severity or treatment efficacy. In many countries, the pandemic had experienced two waves to date. To our knowledge, no studies have compared the CFR between the two waves. In this work, we reported the CFR of 53 countries or regions with the highest COVID‐19 death tolls. Of them, 43 had lower CFR estimates in the ongoing second wave than in the first wave. We discussed the possible reasons. Also, we compared the two‐wave pattern of COVID‐19 with those of influenza. Influenza activities in the pre‐pandemic era provided an indicator for seasonality of climate in a country. The sharp drop in influenza activities in 2020 could an indicator of the effects of social distancing.